Effect of Temperature on Physico-Mechanical Properties of Chunar Sandstone, Mirzapur, U.P., India - Singh A.; Verma A.K.; Kumar A.; Singh C.S.; Roy S.K. (My University, 2025)
Abstract: In this paper, the effect of elevated thermal treatment on the physico-mechanical parameters of Chunar sandstone from Mirzapur district of U.P. was investigated. The studied area is represented geologically by the Vindhyan Supergroup from Meso to Neproterozoic age. Sandstone of Chunar area, Mirzapur, U.P. has been granted the tag of Geographical Indication (GI) under the category of natural goods in 2019. Mechanical strength tests (indirect tensile and uniaxial compressive strength) were performed by a universal testing machine. Samples were treated at elevated temperature in the electric furnace at different temperatures for conducting mechanical and physical tests in each sample and results were recorded. The results suggest that for sandstone, high temperature treatment leads to volume expansion, weight reduction and a decrease in density as well as the reduction in the strength characteristics. Up to 200 °C there is an inappreciable increase in indirect tensile strength and compressive strength but after 200 °C strength gradually decreases. Beyond 400 °C, the P-wave velocities showed a sharp decline due to elevated temperature treatment induced cracks in the heated sandstone. © 2023, Pleiades Publishing, Ltd.